2017
DOI: 10.2135/cropsci2017.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hyperspectral Image Data Outperforms Vegetation Indices in Prediction of Maize Yield

Abstract: Hyperspectral cameras can provide reflectance data at hundreds of wavelengths. This information can be used to derive vegetation indices (VIs) that are correlated with agronomic and physiological traits. However, the data generated by hyperspectral cameras are richer than what can be summarized in a VI. Therefore, in this study, we examined whether prediction equations using hyperspectral image data can lead to better predictive performance for grain yield than what can be achieved using VIs. For hyperspectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
76
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 36 publications
11
76
2
Order By: Relevance
“…Moreover, computer vision with its advantages of high precision and intelligence attracted it as an alternative to human inspection. This technology was a dramatic boost for pest detection (Boissard et al, 2008;Shahin and Symons, 2011;Ding and Taylor, 2016;Senthilkumar et al, 2017), growth monitoring (Clevers and Leeuwen, 1996;Chaerle and Straeten, 2000;Wang et al, 2013;Silva et al, 2014), yield prediction (Salazar et al, 2007;Dunn and Martin, 2010;Aggelopoulou et al, 2011;Aguate et al, 2017) and species recognition (Neuman et al, 1987;Lópezgranados et al, 2006;Tellaeche et al, 2011;Pantazi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, computer vision with its advantages of high precision and intelligence attracted it as an alternative to human inspection. This technology was a dramatic boost for pest detection (Boissard et al, 2008;Shahin and Symons, 2011;Ding and Taylor, 2016;Senthilkumar et al, 2017), growth monitoring (Clevers and Leeuwen, 1996;Chaerle and Straeten, 2000;Wang et al, 2013;Silva et al, 2014), yield prediction (Salazar et al, 2007;Dunn and Martin, 2010;Aggelopoulou et al, 2011;Aguate et al, 2017) and species recognition (Neuman et al, 1987;Lópezgranados et al, 2006;Tellaeche et al, 2011;Pantazi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jarquin et al [10] utilized the reaction norm model for genomic prediction where the genetic and environmental values were replaced by the regression on the markers, and in the interaction between the markers and the environmental covariates, respectively. Dealing with high-throughput phenotypic information, several authors [11][12][13] have shown improvements in predictive ability with the inclusion of these sources of information in the models for wheat and maize. Montesinos-Lopez et al [14] showed that accounting for the band (hyper-spectral image data)-by-environment interaction also improved yield predictability in wheat when compared with those models that did not include this component in the models.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a strong correlation of sugarcane stalk population and yield with normalised difference vegetation index (NDVI) and reflectance at specific wavelengths was reported, suggesting that canopy reflectance measurements at the early growth stage can be used as a screening tool to estimate yield potential [15]. In maize, combining data from 62 wavebands and vegetation indices measured across multiple times using aerial phenotyping lead to an increase in prediction accuracy compared with using single-time-point data [16].…”
Section: Introductionmentioning
confidence: 99%